Transformational Leadership and Teacher Performance as Catalysts for Academic Engagement and Career Self-Efficacy in Vocational Education: A Structural Equation Modeling Analysis in Indonesian Context - Irma Septiana; Muammar (Politea : Jurnal Politik Islam, 2026)
This empirical study investigates the structural relationships among principals’ transformational leadership, teacher performance, academic engagement, and career self-efficacy among vocational education students in Indonesia. Grounded in Bandura’s self-efficacy theory and the Bass-Avolio transformational leadership framework, the study develops an integrated model linking organizational and psychological factors within vocational education contexts. A cross-sectional survey was conducted involving 222 students in grades XI and XII at SMKN 2 Lingsar. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that transformational leadership significantly predicts academic engagement (β = 0.32, p < 0.01) and indirectly affects career self-efficacy through academic engagement mediation (β = 0.12, p < 0.01). Teacher performance emerged as the strongest predictor of academic engagement (β = 0.41, p < 0.001) and significantly influenced career self-efficacy (β = 0.27, p < 0.01). Furthermore, academic engagement demonstrated a strong positive effect on career self-efficacy (β = 0.38, p < 0.001), explaining 62% of the variance in students’ career self-efficacy. The study highlights that vocational graduate unemployment may stem not only from limited technical competence but also from inadequate psychological readiness. Theoretically, this research contributes an integrated framework connecting educational management and educational psychology. Practically, the findings identify strategic school-level interventions to strengthen students’ employment readiness through leadership, teacher effectiveness, and academic engagement development.